Transformasi Karakter Anak: Rahasia Sukses dalam Membentuk Karakter AUD Melalui Pendidikan di Rumah - Hanurawati, Putri Cicilia; Aprily, Nuraly Masum; Qonita, Q; Mulyana, Edi Hendri (Early Childhood Research Journal (ECRJ), 2023)
Instilling character education in early childhood is one of the responsibilities of parents. Character education must be implemented from an early age to shape children into independent human beings, individuals with noble character. The purpose of this study is to describe the character formation of early childhood through education at home or by the family. This research method uses a qualitative approach. Data collection techniques use literature studies using various articles, books, and other sources as data sources. The research results show that the success of character formation in children depends on parenting and support from the environment to form positive character in early childhood. A parenting style that give precedence to frankness and supportive support from parents develops children's positive characters.